Cholesterol-lowering therapy with pravastatin in patients with average cholesterol levels and established ischaemic heart disease: is it cost-effective? - Glasziou, P; Eckermann, S; Mulray, SE; Simes, R; Martin, A; Kirby, A; Hall, J; Caleo, S; White, H; Tonkin, A (2002)
OBJECTIVE: To measure the cost-effectiveness of cholesterol-lowering therapy with pravastatin in patients with established ischaemic heart disease and average baseline cholesterol levels. DESIGN: Prospective economic evaluation within a double-blind randomised trial (Long-Term Intervention with Pravastatin in Ischaemic Disease [LIPID]), in which patients with a history of unstable angina or previous myocardial infarction were randomised to receive 40 mg of pravastatin daily or matching placebo. PATIENTS AND SETTING: 9014 patients aged 35-75 years from 85 centres in Australia and New Zealand, recruited from June 1990 to December 1992. MAIN OUTCOME MEASURES: Cost per death averted, cost per life-year gained, and cost per quality-adjusted life-year gained, calculated from measures of hospitalisations, medication use, outpatient visits, and quality of life. RESULTS: The LIPID trial showed a 22% relative reduction in all-cause mortality (P < 0.001). Over a mean follow-up of 6 years, hospital admissions for coronary heart disease and coronary revascularisation were reduced by about 20%. Over this period, pravastatin cost $A4913 per patient, but reduced total hospitalisation costs by $A1385 per patient and other long-term medication costs by $A360 per patient. In a subsample of patients, average quality of life was 0.98 (where 0 = dead and 1 = normal good health); the treatment groups were not significantly different. The absolute reduction in all-cause mortality was 3.0% (95% CI, 1.6%-4.4%), and the incremental cost was $3246 per patient, resulting in a cost per life saved of $107 730 (95% CI, $68 626-$209 881) within the study period. Extrapolating long-term survival from the placebo group, the undiscounted cost per life-year saved was $7695 (and $10 938 with costs and life-years discounted at an annual rate of 5%). CONCLUSIONS: Pravastatin therapy for patients with a history of myocardial infarction or unstable angina and average cholesterol levels reduces all-cause mortality and appears cost effective compared with accepted treatments in high-income countries.